Tugas dan Wewenang Badan Pengawas Pemilihan Umum dalam Mengatasi Sengketa Pemilu Presiden dan Wakil Presiden - Rahmiz, Faramadinah; Yasin, H. M. (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to determine the extent to which the Bone Regency General Election Supervisory Agency's duties and authority in overseeing the implementation of the General Election, especially to resolve disputes for the 2019 Presidential and Vice-Presidential Elections. Besides, this study also aims to determine what factors alone affect or hinder the implementation of supervision in the General Election held by the Regional General Election Commission of Bone Regency. This research uses empirical and normative research methods. The data obtained were processed and analyzed both qualitatively and quantitatively. The research results show that the implementation of supervision by the General Election Supervisory Agency of Bone Regency on the implementation of the General Election, especially for resolving the 2019 Presidential and Vice-Presidential Election disputes has been running following the applicable laws and regulations. Besides, the Bone Regency General Election Supervisory Body handles election cases and disputes, both administrative, ethical violations, and election criminal offences. The factors that influence the implementation of supervision by the General Election Supervisory Agency of Bone Regency include limited personnel or supervisory apparatus and limited infrastructure, such as the Bone Regency General Election Supervisory Agency's office which has a contract status.